Increased incidence of true type I diabetes acquired during pregnancy. Issue 6567 (31st January 1987) - Buschard, K; Buch, I; Mølsted-Pedersen, L; Hougaard, P; Kühl, C
Abstract : A longitudinal study was carried out of all patients with newly acquired insulin dependent diabetes during pregnancy (as distinct from non-insulin-dependent gestational diabetes) seen at the Copenhagen Centre for Diabetes and Pregnancy during 1966 to 1980. The series comprised 63 patients with a mean age of 27 (SEM 1) years. At diagnosis the mean fasting blood glucose concentration was 15.6 (1.3) mmol/l and mean maximal insulin dose 49 (3) IU/day. At a prospective follow up examination a mean of 8 (SEM 1) years after diagnosis 46 of 60 patients (77%) were being treated with insulin (35 (2) IU/day) and had a very low mean stimulated plasma C peptide value (0.12 (0.02) nmol/l) suggesting absent or nearly absent beta cell function. The remaining 14 patients (23%), not currently receiving insulin, appeared to be severely glucose intolerant, having a mean fasting blood glucose concentration of 13.4 (1.2) mmol/l. Thus most of these patients developing insulin dependent diabetes during pregnancy had true type I disease. Compared with the age specific incidence of type I diabetes in the background population of women the incidence was at least 70% higher in pregnant than non-pregnant women (p less than 0.001; chi 2 = 11.6; f = 1). This increased incidence occurred in the third trimester when the risk of developing type I diabetes was 3.8 times that of non-pregnant women (p less than 0.000001; chi 2 = 35.6; f = 1). Finally, the risk of developing insulin dependent diabetes during pregnancy was lower when conception occurred in the winter (p less than 0.05; chi 2 = 4.18; f = 1).